Analisis Paket Kebijakan Pemerintah di Sektor Perpajakan terhadap Penghasilan Karyawan - Bambang Hermanto (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2016)
By the year of 2015, the government has issued the tax regulation of PPh Article 21 trough the Regulation of Finance Minister (PerMenKeu) No. 122/PMK.010/2015 and the Regulation of Director General of Taxes No. PER-32/PJ/2015 about the amount of Income Non Tax (PTKP). This regulation has a very great positive impact towards both Employee and Company. Therefore, this regulation is believed to be accepted by all sides whether it is for the employee or Company. For the employees, earning up to Rp. 4.000.000,- will not be taxable for the PPh Article 21 For the employees, earning up to Rp. 10.000.000,- the tax will be decreased from 20 % until 32,3 % per month. The impact of tax deregulation positively won’t be affected the Company because the tax is charged to the earning receiver.